2003
DOI: 10.1074/jbc.m301243200
|View full text |Cite
|
Sign up to set email alerts
|

A3 Adenosine Receptor Activation in Melanoma Cells

Abstract: The incidence of melanoma in humans has increased steadily over the past years and is one of the more difficult neoplasias to clinically manage. Due to the limited response of malignant melanoma to conventional chemotherapy and the poor prognosis of patients with metastatic melanoma, new therapies for this disease are needed.Our earlier studies demonstrated that IB-MECA, 1 a stable agonist to A3AR, inhibits the proliferation of neoplastic cells including metastatic melanoma (1-3). A3AR belongs to the family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 27 publications
2
38
1
1
Order By: Relevance
“…Assessment by analytical HPLC of the stability of the monomeric arms containing AR ligands (14,18) in the presence of either CHO or human embryonic kidney 293 cell membranes Assay solutions containing a monomeric arm (diluted from a 5-mM DMSO stock solution of either 14 or 18, 10 μM final concentration) and either Chinese hamster ovary (CHO) or human embryonic kidney 293 (HEK293) cell membrane suspensions (100 μg/mL) were prepared in 50 mM Tris-HCl (pH 7.5) and 10 mM MgCl 2 buffer. The solutions in glass culture tubes (20×75 mm) were incubated at 25°C for 1 h in a shaking water bath.…”
Section: Ultrapurification Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessment by analytical HPLC of the stability of the monomeric arms containing AR ligands (14,18) in the presence of either CHO or human embryonic kidney 293 cell membranes Assay solutions containing a monomeric arm (diluted from a 5-mM DMSO stock solution of either 14 or 18, 10 μM final concentration) and either Chinese hamster ovary (CHO) or human embryonic kidney 293 (HEK293) cell membrane suspensions (100 μg/mL) were prepared in 50 mM Tris-HCl (pH 7.5) and 10 mM MgCl 2 buffer. The solutions in glass culture tubes (20×75 mm) were incubated at 25°C for 1 h in a shaking water bath.…”
Section: Ultrapurification Methodsmentioning
confidence: 99%
“…There are four known subtypes of adenosine receptors (ARs), which belong to the superfamily of GPCRs, referred to as A 1 , A 2A , A 2B , and A 3 -each of which has a unique pharmacological profile, tissue distribution, and combination of effects [12,13]. An agonist of the A 3 AR is currently in clinical trials for hepatocellular carcinoma [13,14]. Fishman et al reported that growth of melanoma cells can be inhibited by activation of A 3 AR via deregulation of the NFκB and Wnt pathways [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations